Teacher Explorations of Science and Science Learning Generate Insights Into Inquiry and Teaching (LEARNing Landscapes, 2011)
Education and science faculty describe explorations introduced into a multi-year professional development program to promote teachers’ abilities to create environments for the elementary and middle school students they teach which elicit learners’ exploratory behavior and sustain them in authentic scientific inquiry. Experiences, which were informed by the teaching-learning research pedagogy of critical exploration (Duckworth, 2006a), involved teachers as co-collaborators and explorers of scientific phenomena and students’ science learning.
Keywords: science; education; professional development; exploratory behavior; inquiry; teaching-learning research; critical exploration; teacher